2015
DOI: 10.1016/j.biopsych.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Basal Hippocampal Activity and Its Functional Connectivity Predicts Cocaine Relapse

Abstract: BACKGROUND Cocaine-induced neuroplastic changes may result in a heightened propensity for relapse. Using regional cerebral blood flow (rCBF) as a marker of basal neuronal activity, this study assessed alterations in rCBF and related resting state functional connectivity (rsFC) to prospectively predict relapse in patients following treatment for cocaine use disorder (CUD). METHODS Pseudocontinuous arterial spin labeling functional magnetic resonance imaging and resting blood oxygen level-dependent functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 79 publications
2
63
0
Order By: Relevance
“…Low insular perfusion indicates a hypo-status induced by the over-stimulation of drug to those involved brain functionalities. We didn’t find hypoperfusion in parahippocampus, which is the only suprathreshold region shown in (Adinoff et al, 2015). This discrepancy may reflect a difference in inter-subject variances between our study and theirs.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Low insular perfusion indicates a hypo-status induced by the over-stimulation of drug to those involved brain functionalities. We didn’t find hypoperfusion in parahippocampus, which is the only suprathreshold region shown in (Adinoff et al, 2015). This discrepancy may reflect a difference in inter-subject variances between our study and theirs.…”
Section: Discussionmentioning
confidence: 65%
“…In drug addiction, we have used ASL MRI to probe the cue-induced activation and abstinence-induced activation in smoking (Franklin et al, 2011; Franklin et al, 2007; Wang et al, 2007b; Wang et al, 2008b), but ASL MRI still remains underexplored in cocaine addiction studies (Question No. 3) with only two publications (Adinoff et al, 2015; Adinoff et al, 2016) which found hypoperfusion only in the parahippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…In fMRI studies, hippocampal activation and network connectivity has been shown to predict cocaine relapse. 12 Limbic connectivity between the hippocampus and the amygdala is also associated with reduced adaptive emotional processing in maltreated individuals with methamphetamine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…10 Connectivity between the amygdala and the hippocampus is associated with maladaptive emotional processing, 11 and alterations in hippocampal network activation and connectivity have been shown to predict relapse. 12 The prefrontal cortex has extensive connections with subcortical structures that regulate emotional processing, including the amygdala. 13 Alcohol and drug exposure impairs emotion regulation in this region, with interconnected medial and cingulate networks showing enhanced reactivity to arousing stimuli and reduced capacity to suppress negative affect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation